2021
DOI: 10.18601/01207555.n29.10
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the intention to adopt a pro- environmental behavior by tourist operators of a Mexican national marine park

Abstract: Los operadores turísticos pueden contribuir a la conservación del ambiente en áreas marinas protegidas por medio de mensa­jes relacionados con el comportamiento esperado por parte del visitante, así mismo, mencionando los posibles impactos de sus acciones en el ambiente marino, pero, sobre todo, presentando un comportamiento eco­lógico. A pesar de la importancia que tiene el comportamiento proambiental en la pro­tección del ambiente, existen pocos estudios que expliquen la formación de este compor­tamiento en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The standard estimates showed perceived behavioral control as the strongest predictor, which was similar to García Mejías et al [ 31 ] and Lin [ 74 ] but different from Nie et al [ 33 ], Yuriev et al [ 36 ] and Swaim et al [ 62 ]. Discussions with undergraduates from revealed that implementation of environmental education since elementary schools equipped students with a strong and positive attitude of environmental protection (mean of 4.47 according to Table 4 ), which did not translate into either environmental protection intention or environmental protection behaviors, a phenomenon known as the debunked “knowledge-attitude-behavior theory,” which were widely observed [ 80 ].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The standard estimates showed perceived behavioral control as the strongest predictor, which was similar to García Mejías et al [ 31 ] and Lin [ 74 ] but different from Nie et al [ 33 ], Yuriev et al [ 36 ] and Swaim et al [ 62 ]. Discussions with undergraduates from revealed that implementation of environmental education since elementary schools equipped students with a strong and positive attitude of environmental protection (mean of 4.47 according to Table 4 ), which did not translate into either environmental protection intention or environmental protection behaviors, a phenomenon known as the debunked “knowledge-attitude-behavior theory,” which were widely observed [ 80 ].…”
Section: Discussionsupporting
confidence: 78%
“…García Mejías et al [ 31 ] examined factors influencing the intention to take up environmental protection behaviors by tourist operators. Results listed perceived behavioral control as the most significant predictor, followed by subjective norms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each construct, as shown in Table 3, was rated based on five-point Likert scale questions, whereby 1 indicated "strongly disagree" or "never" and 5 indicated "strongly agree" or "always", producing well-defined and measured results. The measures of norms and efficacy were modified from previous studies [41][42][43][44][45], while the measures of environmental awareness, attitudes and behavior were created based on previous studies [43][44][45][46][47] and discussions with university personnel involved with environment protection policies. To analyze the collected data, descriptive statistics were carried out using the software tool SPSS 25.0 [48].…”
Section: Methodsmentioning
confidence: 99%